واقع تمويل البنوك التجارية للمشاريع االستثمارية الفالحية في ظل استراتيجية التنويع االقتصادي .دراسة حالة بنك الفالحة و التنمية الريفية BADR - خرشي اية; غريب وليد (جامعة المسيلة, 2020)
قامت الجدائخ في الدشػات األخضخة بسجسػعة مغ اإلصالحات ك التي تيجؼ إلى التشػيع في االقتراد كاالىتساـ بسختمف السذاريع االستثسارية خارج قصاع السحخكقات ،ىاتو اإلصالحات تسكشيا مغ تػفضخ مػارد مالية ال يدتياف بيا. إذ ما تع القزاء عمى العخاقضل التي تقف عائق في سبضل تخقضتضيا ،كعمى رأسيا صعػبة الحرػؿ عمى القخكض السرخؼية كىحا ما أدػ إلى عجـ تصػر كتػسيع في مثل ىحه السذاريع، كىحا الػضع جعل مغ الجكؿ تقػـ بتدصضخ مجسػعة مغ البخامج، كالتي تخجست في شكل ىضئات لتشفضح سياستيا االستثسارية مغ جية،كدعع السدتثسخيغ مغ جية أخخػ. كيختبط دكر اليضئات بالجكر الحؼ تمعبو البشػؾ العسػمية مغ خالؿ تقجيسيا لمقخكض السرخؼية،كالتي مكغ السدتثسخيغ مغ إقامة مذاريعيع االستثسارية،كمغ خالؿ مداىسة أحج ىحه البشػؾ في تسػيل السذاريع االستثسارية الفالحية ،كالستسثل في, بشظ الفالحة كالتشسية الخيؽية–ككالة السدضمة–الحطشا أف الشتائج السحققة في مجاؿ تسػيل السذاريع االستثسارية عمى العسػـ مقبػؿ،رغع الرعػبات التي تػاجو البشػؾ،كالستسثمة في تعثخ القخكض السقجمة.In recent years, Algeria has undertaken a set of reforms that aim to diversify the economy and pay attention to various investment projects outside the hydrocarbon sector. These reforms enable it to provide significant financial resources. As the obstacles that stand in the way of my promotion have not been eliminated, on top of which is the difficulty in obtaining bank loans, and this has led to the lack of development and expansion in such projects, and this situation has made countries establish a set of programs, which were translated into bodies to implement their policy Investment on the one hand, and investor support on the other hand. The role of the organizations is linked to the role that public banks play by providing bank loans, which enabled investors to set up their investment projects, and through the contribution of one of these banks in financing agricultural investment projects, namely, the Bank for Agriculture and Rural Development - Al-Messila Agency - we noted that the results achieved in The field of financing investment projects is generally acceptable, despite the difficulties that banks face, represented by the failure of the loans provided.
Keywords: القصاع ألفالحي، التشػيع االقترادؼ، التشسية االقترادية، استثسار السذاريع، تسػيل، بشػؾ تجارية، مذاريع.بشظ الفالحة ك التشسية الخيؽية.the agricultural sector, economic diversification, economic development, project investment, financing, commercial banks, projects, the agricultural and rural development bank